Functional Characterization of Human CYP2C9 Allelic Variants in COS-7 Cells - Du, Huihui; Wei, Zhiyun; Yan, Yucai; Xiong, Yuyu; Zhang, Xiaoqing; Shen, Lu; Ruan, Yunfeng; Wu, Xi; Xu, Qingqing; He, Lin; Qin, Shengying (Frontiers in Pharmacology, 2016)
Variability in activity of CYP2C9, which is involved in the metabolism of approximately 15% of current therapeutic drugs, is an important contributor to interindividual differences in drug response. To evaluate the functional alternations of CYP2C9*2, CYP2C9*3, CYP2C9*8, CYP2C9*11 and CYP2C9*31, identified in our previous study in Chinese Han population, allelic variants as well as the wild-type CYP2C9 were transiently expressed in COS-7 cells. Kinetic parameters (Km, Vmax and Clint) for S-warfarin 7-hydroxylation by these recombinant CYP2C9s were determined. Relative to CYP2C9.1, recombinant CYP2C9.3 and CYP2C9.11 exhibited significantly higher Km values, and all allelic variants showed significantly decreased Vmax and Clint values. Among all allelic variants, catalytic activity of CYP2C9.3 and CYP2C9.11 reduced the most (8.2% and 9.8% of Clint ratio, respectively; P<0.001). These findings should be useful for predicting the phenotype profiles of CYP2C9 in Chinese Han population, comparing the functional results of these alleles accurately, and finally optimizing pharmacotherapy of drug treatment.